2015
DOI: 10.1007/s00384-015-2165-2
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance after neoadjuvant therapy in advanced rectal cancer with complete clinical response can have comparable outcomes to total mesorectal excision

Abstract: Active surveillance can be a safe option that avoids the morbidity associated with proctectomy and preserves oncologic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 17 publications
3
45
0
4
Order By: Relevance
“…Observation group patients seemed to be older than those in the radical surgery group [2, 4, 79, 13]. Except for one observation group patient with liver metastasis in Smith et al [8], no patients had distant metastasis (DM) according to the study descriptions. Most patients had medial/distal and locally advanced rectal cancer.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Observation group patients seemed to be older than those in the radical surgery group [2, 4, 79, 13]. Except for one observation group patient with liver metastasis in Smith et al [8], no patients had distant metastasis (DM) according to the study descriptions. Most patients had medial/distal and locally advanced rectal cancer.…”
Section: Resultsmentioning
confidence: 98%
“…Reports from Habr-Gama's group and others are not consistent regarding the time point for assessment of sustained cCR, which ranged from 12 to 14 months after NCRT completion, or regarding the time point for identifying patients failing to maintain cCR [2, 3, 5, 6, 8, 9, 20]. Only seven studies established a rigorous follow-up system (Table 6), and they suggested that cCR should only be considered sustained after at least 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…1327 Eight studies reported data for an adequate control proctectomy group, but there was significant variation. Four used a post-surgical pathological complete response (pCR) group for comparison 14,16,25,26 , 2 used cCR tumors undergoing surgery, 19,20 1 used both, 22 and 1 used a surgical group matched for clinical stage (regardless of tumor response). 23 Outcome data for incomplete response, non-response, and local excision were excluded from comparisons as these were not regarded as adequate control group data.…”
Section: Resultsmentioning
confidence: 99%
“…6 Emerging data suggest that certain low-risk tumors may be appropriate candidates for this strategy. 711 However, it is well established that cCR does not equate to pCR as residual tumor may be identified in up to 75 % of resected specimens where the gross tumor has clinically disappeared. 12,13 Furthermore, even among patients with complete pathologic resolution of the primary tumor, residual nodal disease is present in up to 15 % of cases 14,15 and is an independent predictor of poor outcomes.…”
mentioning
confidence: 99%